ANALISIS KESULITAN MENYELESAIKAN SOAL CERITA MATERI BILANGAN PECAHAN KELAS V SD ISLAM AL-RAUDLATUL AMIEN GRESIK - Siti Choiriyah; Umi Hanik (Jurnal Sosial Humaniora dan Pendidikan, 2024)
This research aims to find out what difficulties students experience when working on fractional number story problems. This research uses descriptive qualitative research methods. The subjects in this research were fifth grade students at Al-Raudlatul Amien Gresik Islamic Elementary School. The researcher took 3 students as subjects who had high, medium and low levels of ability. The data collection process was carried out using interviews and documentation study. This research uses 4 indicators to determine students' difficulties, namely 1) students have difficulty understanding questions, 2) students have difficulty changing word problems into mathematical form, 3) students have difficulty calculating and, 4) students have difficulty writing conclusions or final answers. The results of this study show that subjects with high abilities do not experience difficulty in solving questions. Subjects with moderate abilities experience difficulty when changing the form of mixed fractions to improper fractions. Subjects with low ability have difficulty understanding story problems, have difficulty changing story problems into mathematical form, have difficulty calculating, and have difficulty writing conclusions or final answers